ANALYSIS OF THE INFLUENCE OF BUSINESS RISK, LIQUIDITY, AND SOLVENCY ON STOCK RETURNS WITH PROFITABILITY AS AN INTERVENING VARIABLE IN LOGISTICS AND DELIVERIES SUB-SECTOR TRANSPORTATION COMPANIES - Ulfa Safara; Nekky Rahmiyati (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This research aims to determine business risk, liquidity and solvency on stock returns with profitability as an intervening variable in the logistics and deliveries sub-sector on the Indonesia Stock Exchange for the 2019-2022 period. Data collection techniques using company annual report documentation. This research is quantitative research, the population in this research is all logistics and deliveries sub-sector companies registered on the IDX in 2019-2022, and the sampling technique chosen was purposive sampling. The collected data was analyzed using SmartPLS (Partial Least Square) analysis. The research results show that business risk has a significant effect on profitability. However, business risk has no significant effect on stock returns. Liquidity has a significant effect on profitability, but liquidity does not have a significant effect on stock returns. Solvency has a significant effect on profitability, but solvency has no significant effect on stock returns. Profitability has no significant effect on stock returns. Profitability has no effect as an intervening variable on the effect of business risk on stock returns, the effect of liquidity on stock returns, and the effect of solvency on stock returns.